RELIGIOUS MODERATION - Fakhruddin Azmi, Saripuddin Daulay (Yayasan Pendidikan Islam dan Multikultural, 2022)
Abstract This Discussion Aims To Add To The Treasures And Insights And understanding of religious moderation, which is a conception of great value highly recommended by Allah swt; even Allah swt calls this religious moderation as Wasathiyah. The method in this journal is to use a literature review. The Literature Review is a description of the theory, findings and other research materials obtained from reference materials to be used as a basis for research activities to develop a clear frame of mind from the formulation of the problem to be studied. someone else has done before. There are good wasathiyah/moderate principles for the continuation of a peaceful and loving life. These principles include Tawazzun (balance), I'tidal (straight and firm), Tasamuh (tolerance), Tawassuth (taking the middle way), Shura(deliberation), Ishlah (reform), Tahadhdhur (civilized), Musawah (egalitarian), Aulawiyah (putting priority on priority), Tathawwur wa Ibtikar (dynamic and innovative). The values ​​of moderation contained above are applied in the regeneration process through Islamic education so that in the future, there will be more plurality generations who uphold the principle of equality and mutual respect for differences; the more generations will emerge who love the diversity in religion so that Indonesia becomes a Baldatun Thoyyibatun Wa Rabbun Ghafur.